Gestational protein malnutrition impairs c-myc and p63 protein expression, increases prostatic intraepithelial neoplasia incidence and prostatitis aggressiveness in adult male offspring subjected to hormonal handling - Rinaldi, Jaqueline C. [UNESP]; Felisbino, Sergio Luis [UNESP]; Amorim, Renee Laufer [UNESP]; Scarano, Wellerson Rodrigo [UNESP]; Favaro, Wagner Jose; Justulin, Luis Antonio [UNESP] (Amer Assoc Cancer Research, 2014)
Background: Prostate cancer is the second most common cancer diagnosed in men; however its etiology remains unknown. Previous studies have shown that environmental adverse factors, such as maternal nutritional status during pregnancy, can influence fetal development and predispose people to diseases in adult life. The feeding of low-protein diets to pregnant rats result in fetal growth disturbance, androgen/estrogen unbalance and changes in the expression and sensibility of hormone receptors in male offspring. These alterations can promote permanent changes in androgen dependent organs, such as in the prostate. In this sense, we hypothesized that the hormonal unbalance that occurs during aging can lead to an increase in the susceptibility to prostatic disorders. Aim: To evaluate our hypothesis, malnourished male rat offspring were submitted to simultaneous estrogen and testosterone exposure in adulthood, to drive lesions in the rat ventral prostate gland (VP). Methods: 17 week-old Wistar rats (n=48) that received in utero normal protein diet (NP group, AIN93G=17% protein) or low protein diet (RP group, AIN93G modified=6% protein) were given implants with 17β-estradiol plus testosterone administration (NPH and RPH groups) for 17 weeks. The animals were killed at the age of 34 weeks and the VP were excised, weighted and processed for histopathological, immunohistochemical (Ki67, AR, p63, e-caderin, laminin, c-myc and GSTP), biochemical and ultrastructural analysis. Results: Both absolute and relative VP weight from NPH animals were about 30% higher than RPH. Serological data showed that estradiol levels were similar in both groups, but testosterone levels were lower in the RPH male offspring. The steroid hormone exposure in adult life promoted prostate lesions in both RPH and NPH offspring associated with reactive stroma. VP from RPH group exhibited heightened susceptibility to prostatic intraepithelial neoplasia (mainly cribriform and signet ring-cell patterns) and increased the incidence and aggressiveness of prostatitis. In this group, a higher proportion of basal cells, increased proliferation index, lower expression ofthe androgen receptor and increased focus of collagenous micronodules closely associated to epithelial neoplasias were also observed. Conclusion:These observations suggest that maternal protein restriction alters adult prostate response to androgen/estrogen handling and increases susceptibility to prostate diseases. Ethical protocol:CEEA,476/2013 IBB-UNESP; Funding Support: 2009/50204-6 and 2013/09649-0.